2021
DOI: 10.1111/ppl.13304
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds produced by Pseudomonas pseudoalcaligenes alleviated drought stress by modulating defense system in maize (Zea mays L.)

Abstract: Research on plant growth-promoting bacteria (PGPR) revealed an effective role of bacterial volatile organic compounds (VOCs) in stress alleviation. Out of 15 PGPR strains, infection with VOCs from Pseudomonas pseudoalcaligenes' resulted in maximum germination, growth promotion, and drought tolerance in maize plants. The VOCs of P. pseudoalcaligenes caused induced systemic tolerance in maize plants during 7 days of drought stress. The VOCs exposed plants displayed resistance to drought stress by reducing electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…2,3-butanedione was decreased in (S)reutericyclin fed mice. It is a plant-growth promoting compound [36] emitted from Bacillus subtilis [37] and has been reported in the headspace of Pseudomonas pseudoalcaligenes [38] and Bacillus mojavensis [36] cultures, but was not previously reported in fecal samples of mice. Among other substances 2-heptanone showed elevations in tissue and fecal samples of dairy cattle and goats infected with Mycobacterium avium subspecies paratuberculosis [39].…”
Section: Discussionmentioning
confidence: 94%
“…2,3-butanedione was decreased in (S)reutericyclin fed mice. It is a plant-growth promoting compound [36] emitted from Bacillus subtilis [37] and has been reported in the headspace of Pseudomonas pseudoalcaligenes [38] and Bacillus mojavensis [36] cultures, but was not previously reported in fecal samples of mice. Among other substances 2-heptanone showed elevations in tissue and fecal samples of dairy cattle and goats infected with Mycobacterium avium subspecies paratuberculosis [39].…”
Section: Discussionmentioning
confidence: 94%
“…BRISH6 mitigates the toxic effect of deficit water stress and lowered levels of components of the antioxidative defense system, viz., SOD, CAT, APX, POD, GPX, and polyphenol oxidase, in Zea mays [ 20 ]. Similarly, PGPR strain P. pseudoalcaligenes alleviated water stress in Z. mays and enhanced antioxidant defense enzyme levels by modulating the defense system under different levels of water stress [ 21 ]. Likewise, plants treated with drought tolerating strains of Bacillus species acquired drought resistance by lowering the activity of antioxidant enzymes such as APX and GR [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many recent studies have demonstrated the importance of PGPR, such as Ochrobactrum sp. [ 20 ] and Pseudomonas pseudoalcaligenes [ 21 ], for the amelioration of drought stress in edible crops. For example, when drought-tolerant PGPR strains were administered as soil inoculants to maize plants grown in a water deficit environment, they significantly improved the growth, root elongation, and NPK uptake by reducing ethylene levels in plants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also improved the chemical composition of essential oils (Çakmakçı et al 2020). The application of Pseudomonas pseudoalcaligenes enhanced the phytohormones, chlorophyll content antioxidant production and the activities of antioxidant enzymes in Z. mays facing drought stress (Yasmin et al 2021).…”
Section: Discussionmentioning
confidence: 97%